Análise de sustentabilidade do cultivo de algas marinhas em Trairí - Ceará - Fiuza, Ana Beatriz Jucá de Queiroz (2011)
Sustainable development is defined as the process that meets the needs of the present population without compromising the ability to meet the needs of future generations. For society to develop sustainably is necessary to achieve goals such as: economic growth, poverty eradication, ensuring continuity of generations and nature preservation. For an aquacutture be a sustainable system it is necessary that it's economic-social, technological and environmental dimensions integrated and balanced. Therefore, the application of the sustainability concept in an aquaculture requires that the activity to be: productive by adding the externalities to production costs; rationally in the use of natural resources without degrading the ecosystem; and profitable, generating income for the local community, enhancing the quality of life within the community, and respect the local culture. Therefore, the main objective of the present work was to assess the sustainability of the algae cultivation in Trairí, Ceará. To achieve this goal the cultivation of algae were studied focused on four dimensions of sustainability, such as: socio-economic, technological and environmental. The work was defined as a case study and the methodology assessed qualitative and quantitative variables under a descriptive and exploratory approach characterizing the study area and describing indexes and indicators used in the sustainability assessment, and also featuring the environmental quality of the cultivation site. The results for the activity were: Index of Economic and Social Development (IDES - 0,881) of high level; Index of Social Capital (ICS - 750) of medium-level; Index of Technology (IT - 0,850) of medium level; Index of Environment (IA - 0,833) of high level and Index of Sustainability (IS - 0,804) of high level. In the analysis of the cultivation environmental conditions it was observed that these are interrelated and that the area is adequate to the algae cultivation. The investigation of the trace metals in the sediment and cultivated algae showed that Gracilaria Birdiae and Hypnea musciformis concentrated more contaminants and micronutrients than the sediment. Additionally, the analysis of bioaccumulation factor (FBA) among the sediment and algae showed that G. birdiae had the highest FBA of Zn and that H. musciformis had the highest Cu, Pb and Cd FBAs. However, the algae were not contaminated by trace metals, therefore, it was concluded that the cultivation of algae in Trairi is a sustainable productive activity.